Polar Agriculture in the Yamal-Nenets National District during the Great Patriotic War - T. V. Kozelchuk; O. V. Ryabkova (Научный диалог, 2020)
The article is devoted to the history of the development of polar agriculture in the Yamal-Nenets National District during the Great Patriotic War. The questions of the dynamics of expansion of the sown areas of open and protected ground in the specified territory are considered. Based on the analysis of documents preserved in the state archives of the Russian Federation, detailed information on the development and use of sown areas is provided, in particular, the volumes of cultivated and manufactured products are indicated. Attention is paid to the development of collective and individual truck farming in the Yamal-Nenets okrug during the war years. The question is raised about the role of collective farms in the development of polar agriculture in the okrug, in particular, data on collective farms which areas were engaged in crop production are provided. The novelty of the study is seen in the attraction of new historical sources, allowing to enter into scientific circulation data that help to systematize and detail information on the development of polar agriculture in the Yamal-Nenets okrug during the Great Patriotic War. The relevance of the study is due to the scientific and social significance of the works devoted to the development of the Arctic territories of the Russian Federation in significant periods of Russian history. The authors conclude that during the war years in the district there was a leap in the development of the industry.